2022
DOI: 10.1021/acsnano.2c07444
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Destruction and Internal Cascade Synergistic Antifungal Strategy for Fungal Keratitis

Abstract: Fungal keratitis is one of the most common blindness-causing diseases, but clinical antifungal treatment remains a challenge. The fungal cell wall and biofilm matrix which severely confine the drug preparation are the critical obstructive factors to therapeutic effects. Herein, we report ethylenediaminetetraacetic acid (EDTA) modified AgCu2O nanoparticles (AgCuE NPs) to disrupt the cell wall and then eradicate C. albicans through the internal cascade synergistic effects of ion-released chemotherapy, chemodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…742 The existence of biofilms, which hinder the penetration of nanocarriers and reduce drug susceptibility, is one of the significant barriers for clinical trials. 667 Various strategies have been explored to enhance the penetration of drug carriers by introducing targeting membranes, changing the protecting ligands/coatings, and optimizing the size and shape of the carriers. 743−747 Both biodegradability and biocompatibility can be achieved through integration with organic polymers.…”
Section: Chemicalmentioning
confidence: 99%
See 2 more Smart Citations
“…742 The existence of biofilms, which hinder the penetration of nanocarriers and reduce drug susceptibility, is one of the significant barriers for clinical trials. 667 Various strategies have been explored to enhance the penetration of drug carriers by introducing targeting membranes, changing the protecting ligands/coatings, and optimizing the size and shape of the carriers. 743−747 Both biodegradability and biocompatibility can be achieved through integration with organic polymers.…”
Section: Chemicalmentioning
confidence: 99%
“…Since silica-cored Au nanoshells served as the first photothermal nanomaterials for clinical use, more and more inorganic agents with strong absorption in the NIR region, high chemical stability, adjustable water solubility, and minimal cytotoxicity have entered clinical trials. , Clinical trials have also been underway for small organic molecules due to their good biodegradability, good repeatability, and simple preparation. , Nevertheless, the major challenges for the clinical implementation of photothermal nanomaterials are the complex metabolism and excretion behaviors . The representative works on PTT with diverse photothermal nanomaterials in recent years are summarized in Table .…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, AgCuO 2 nanoparticles modified with EDTA were reported for a synergistic photothermal, photodynamic, chemotherapy, and chemodynamic therapy to overcome multi‐drug resistant fungal keratitis. [ 41 ] Another study reported the development of modified hypocrellin using organic cages for combinational photodynamic therapy against multidrug resistant Candida spp. [ 42 ] However, biocompatibility and biodegradability of the nanocarrier is an important prerequisite to potentially qualify into the clinics.…”
Section: Introductionmentioning
confidence: 99%
“…The integrity of the bacterial envelope can maintain the vitality, virulence, and normal functional morphology of the bacteria. , More importantly, the lipid in the membrane bilayer is the key buffer of reactive oxygen species (ROS), which can balance the oxidation and reduction states of the bacteria . A special form of death caused by iron-dependent lipid peroxidation is defined as ferroptosis .…”
Section: Introductionmentioning
confidence: 99%